PENGARUH PEMERIKSAAN, SANKSI DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PEMODERASI PREFERENSI RISIKO - Santi Amalya Amini; Ngadiman (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This study aims to examine the effect of independent variables, namely tax audits, tax sanctions and taxpayer awareness on individual taxpayer compliance with risk preferences as a moderating variable. This study is a quantitative research with research data sourced from distributing questionnaires with a sample size of 100 respondents using the slovin method. The study indicates that only two hypotheses can be accepted, taxpayer awareness influences taxpayer compliance and risk preferences are able to moderate the relationship between tax audits and taxpayer compliance